Cnot4 heterozygosity attenuates high fat diet-induced obesity in mice and impairs PPARγ-mediated adipocyte differentiation - Tomokazu Yamaguchi; Midori Hoshizaki; Yumiko Imai; Tadashi Yamamoto; Keiji Kuba (PLoS ONE, 2025)
Adipocyte differentiation is crucial for formation and expansion of white adipose tissue and is also associated with the pathologies of obesity. CNOT4 is an E3 ubiquitin ligase and also contains RNA binding domain. In mammals CNOT4 has been suggested to interact with CCR4-NOT complex, a major executor of mRNA poly(A) shortening. While several subunits within the CCR4-NOT complex were shown to be involved in obesity and energy metabolism, the roles of CNOT4 in obesity remain unexplored. In this study, we generated and analyzed Cnot4 knockout mice and found that Cnot4 heterozygous (Cnot4 Het) mice exhibit resistance to high fat diet-induced obesity, including significant reduction in adipose tissue mass and hepatic lipid depots. However, Cnot4 Het did not affect mRNA expression of metabolic genes as well as serum lipid levels or glucose tolerance. On the other hand, Cnot4 Het fibroblasts significantly reduced the capability of differentiation into adipocytes and down-regulated adipogenic gene expression compared to wild type fibroblasts. Mechanistically, heterozygous deletion of Cnot4 down-regulated the transcriptional activity through decreased binding of PPARγ to promoter region of the target gene, thereby suppressing up-regulation of adipocyte marker gene expression in response to rosiglitazone, a PPARγ agonist. These results suggest that CNOT4 mediates adipocyte differentiation during formation and growth of adipose tissue partly through positively regulating transcriptional activity of PPARγ.